Penggunaan Alih Kode Pada Pembelajaran Bahasa Indonesia Berperspektif Gender - Bekty Tandaningtyas Sundoro (Jurusan Tadris Bahasa Indonesia, 2020)
The gender difference is one that affects the use of code-switching. This study aims to describe and explain the types and impacts of code-switching used in gender-based learning. The data in this study are in the form of speech events between teachers and students in Indonesian language learning at SMK Negeri 1 Banyumas. Data was collected by paying attention to gender aspects. Sources of data in this study are documents and informants. The technique of data using interview, observation, proficient, and listening method. The data validity technique uses the triangulation technique of data sources and informant reviews. Data analysis used the intralingual matching method. The results showed that the use of codes was more common in classes with male teachers than female teachers. The positive impact of using code-switching by male teachers makes learning more communicative and students seem enthusiastic about participating in learning. The positive impact on classrooms with female teachers makes learning more formal because teachers can minimize the use of code-switching.Perbedaan gender adalah salah satu yang memengaruhi penggunaan alih kode. Penelitian ini bertujuan untuk mendeskripsikan dan menjelaskan jenis dan dampak alih kode yang digunakan dalam pembelajaran berdasarkan gender. Data dalam penelitian ini berupa peristiwa tutur antara guru dan siswa dalam pembelajaran Bahasa Indonesia di SMK Negeri 1 Banyumas. Data dikumpulkan dengan memperhatikan aspek gender. Sumber data dalam penelitian ini adalah dokumen dan informan. Teknik pengumpulan data menggunakan wawancara, observasi, metode cakap dan simak. Teknik validitas data menggunakan teknik triangulasi sumber data dan review informan. Analisis data menggunakan metode padan intralingual. Hasil penelitian menunjukkan penggunaan alih kode lebih banyak dijumpai dalam kelas dengan guru laki-laki dibandingkan guru perempuan. Dampak positif penggunaan alih kode yang dilakukan guru lelaki menjadikan pembelajaran lebih komunikatif dan siswa tampak antusias mengikuti pembelajaran. Dampak positif pada kelas dengan guru perempuan menjadikan pembelajaran lebih formal karena guru dapat meminimalisasi penggunaan alih kode.